CORRELATION AND PATH COEFFICIENT ANALYSIS FOR YIELD AND YIELD COMPONENTS IN BLACKGRAM ( CKGRAM (Vigna mungo igna mungo igna mungo (L.) HEPPER) HEPPER) - AND G. M. LAL, CH. SHALINI (The Bioscan, 2018)
Eighty genotypes along with two national checks ‘T-9’ and ‘Shekhar-2’ were evaluated in Randomized Block Design with three replications. Wide range of variability was observed for quantitative traits. The variability study indicated high to moderate phenotypic and genotypic coefficient of variation accompanied by high heritability and genetic advance as per cent of mean for traits like number of clusters per plant, number of pods per cluster, primary branches per plant, harvest index and seed yield per plant indicating their importance in selection for yield improvement. Seed yield per plant showed strong positive correlation with number of clusters per plant, number of pods per cluster and harvest index, these traits has also showed positive direct effect on seed yield indicated scope for improvement through selection of these traits